Wireless Hazard Badges to Detect Nerve‐Agent Simulants. (6th July 2016) - Zhu, Rong; Azzarelli, Joseph M.; Swager, Timothy M.
Abstract: Human exposure to hazardous chemicals can have adverse short‐ and long‐term health effects. In this Communication, we have developed a single‐use wearable hazard badge that dosimetrically detects diethylchlorophosphate (DCP), a model organophosphorous cholinesterase inhibitor simulant. Improved chemically actuated resonant devices (CARDs) are fabricated in a single step and unambiguously relate changes in chemiresistance to a wireless readout. To provide selective and readily manufacturable sensor elements for this platform, we developed an ionic‐liquid‐mediated single walled carbon nanotube based chemidosimetric scheme with DCP limits of detection of 28 ppb. As a practical demonstration, an 8 h workday time weighted average equivalent exposure of 10 ppb DCP effects an irreversible change in smartphone readout.